Hubungan antara asupan vitamin A, dan vitamin C dengan kadar hemoglobin pasien gagal ginjal kronik - Yoni Wibowo (University of Darussalam Gontor, 2017)
Chronic Renal Failure (CRF) is a disease that has a bad prognosis. It happens when the function of renal decreases gradually. One of the complications that often appears in CRF is anemia or the decrease of hemoglobin level in the blood that is related to the intake of vitamin A and vitamin C. This research’s aims were to investigate the correlation between intake of vitamin A, vitamin C and hemoglobin level in hemodialysis. Type of the research was analytical observational research with cross-sectional approach. Subjects were obtained by consecutive sampling with total research subjects were 22 subjects. Percentages of vitamin A and vitamin C were obtained by recall 3x24 hour method, hemoglobin level was obtained by the Spectrophotometric method. While Pearson Product Moment was used to investigate the correlation. The percentages of outpatients who had an adequate intake of vitamin A and vitamin C were 68,2% and 4,5% respectively. Meanwhile, most of the patients had low hemoglobin level which was 86,4%. There was not any correlation between intake of vitamin A and vitamin C with hemoglobin level.